Polemik in den Schriften Melchior Hoffmans: Inszenierungen rhetorischer Streitkultur in der Reformationszeit - Lundström, Kerstin (Stockholm German and Dutch Studies, 2015)
Polemik in den Schriften Melchior Hoffmans. Inszenierungen rhetorischer Streitkultur in der Reformationszeit" is a study of pamphlets written as a reaction to, and attempt for, expansion of the Lutheran and Zwinglian Reformation. Melchior Hoffman's work has, so far, almost solely been investigated by historians of religion and thus focused merely on religious topics and argumentation, and rather seldomly on the literary aspects of his pamphlets - such as rhetorics, argumentation strategies and text compilation. In order to close this gap of research on Melchior Hoffman and - in the sense of a New Historicism approach - give him as a non-canonical author more attention, this book focuses on the literary qualities of the texts. It is thus the first full-length study on Melchior Hoffman by a literary scholar. Not only has little been written on Melchior Hoffman, but also about lay writers in the Reformation at all. Thus, the book delivers new perspectives within the field of Reformation pamphlet writers. Theoretical significance is an integral part of the study, with a focus on developing a new theoretical concept for analyzing polemic texts. The innovative approach combines post-modern theories like (constructivist) Cultural Studies, and Performativity concepts with Communication Analyses and Classical Rhetorics. By doing so, it provides a unique approach to texts from the 16th century, which can easily and reasonably be applied to polemical texts of the 21st century as well as to even older texts than Hoffman's. The book has been written in the research field of German Literature, but will be of great interest for both literary scholars and historians (of religion or culture).